(untitled) (Research, Society and Development, 2022)
This paper aimed to develop an artisanal multimeter, designed to carry out electrical measurements, and a sequence of investigative teaching. Thus, they were used, among others, the theoretical perspectives of Vygotsky (1999; 2007) and Carvalho (2013), who consider the educational intervention as an aid to the knowledge acquisition. The methodology was applied in two Senior Year Classes of High School with Diploma Program in Buildings incorporated to them in the Federal Institute of Education, Science and Technology from Mato Grosso – Cuiabá Campus. One of them was denominated by Testing Class (TC) and the other by Control Class (CC). In the first one, the contents were worked out, using the educational product in the investigative perspective. In the second one, the traditional teaching model was used. The classes were quantitatively evaluated to verify the equivalence of the knowledge levels and the initial knowledge about the featured subject. At the end, a quantitative evaluation was done in order to investigate in which class there was a greater efficiency in the appropriation of the covered contents. The results showed that assimilation in the TT was more effective, due to the artisanal multitest and the investigative teaching sequence. It is concluded that the didactic strategy of using the educational product, through the SEI, is more effective for assimilating the contents related to electricity.